Advanced STEP parameterised and constrained features for reverse engineering. (15th July 2008) - Remy, Sebastien; Ducellier, Guillaume; Charles, Sebastien; Eynard, Benoit
Reverse Engineering (RE) is a research field where physical models are digitised to be reconstructed, surface by surface, feature by feature, as a CAD model. This paper deals with features known by their mathematical equation, obtained when a touch probe based digitisation is used. The paper presents an interactive approach for RE of mechanical part. It introduces a CAD model reconstruction methodology based on new STEP AP203 ED2 standard integrating parameterised features that enables the parameterisation of the rebuilt features. This is needed for a complete integration of the new CAD model in a collaborative product development approach.